(untitled) (El Hilo de la Fabula, 2021)
The history of Dora Manchado, considered one of the last tehuelche’s speakers, and her relations with the different institutions and researchers who worked beside her, and, also, her dissensual attitudes towards those who gradually approached her over time is a good example of how alternative realities can be constructed depending on on who is documenting and which political, ideological, academic interests may be involved. Dora Manchado lived in the province of Santa Cruz between 1934 and 2018. She spent part of her life in Camuse Aike, in El Calafate, and in Rio Gallegos, and she was cataloged over time in contradictory ways: «deficient informant», «bad informant» or «guardian of the language». She was also considered as a «teacher of Tehuelche» within the education policy project known as «Intercultural Bilingual Education». Indeed, Dora was occupying different spaces according to her silences and elusive responses when interviewed. As an informant, Dora has also been silent. Hence the title of this article, aimed at problematizing the role of informants. This article proposes to recover the figure of Dora as a mediator, according to Ana Teresa Martínez’s proposal (2013).